The Impact of Remuneration toward Salary Satisfaction: A Case Study on Job Evaluation Method in SME Employees in Central Sulawesi, Indonesia - Lestari, Yulian Sri; Fahmie, Arief; Zulaifah, Emi (Journal of Nonformal Education, 2021)
This study aims to evaluate the effectiveness of remuneration with job evaluation point method and to discover its impact toward salary satisfaction of employees in Small and Medium scale Enterprise (SME). This research is a case study involving SME level employees in the field of food and beverage preparation who received remuneration with job evaluation point method. The methods for data collection used in this research were observation, interview, and questionnaires. The measurement scale used was the Pay Satisfaction Questionnaire. This research was an experimental action research with the randomized pretest–posttest control group design. The Mann–Whitney and Friedman tests were applied for conducting data analysis. The study argues that the application of remuneration by using job evaluation point method can increase the satisfaction of SME employees, reduce the level of turnover, and increase work commitment of employees. The results of the data analysis showed that the hypothesis was accepted; there was an improvement in salary satisfaction of experimental group who received remuneration with a significance value of p0.005.